Effect of metacognitive awareness on achievement in foreign language learning - Doğan, Yunus; Tuncer, Murat (My University, 2017)
This study aimed to determine the relationship between general metacognitive awareness and academic achievement in foreign language learning. To this end, the study first tried to investigate whether there were any correlations between the construct of metacognitive awareness and its sub-dimensionsknowledge management, planning, monitoring, evaluation- and the academic achievement in foreign language. The study then went on to search whether metacognition with its sub-dimensions were effective in foreign language achievement. The sample of the study consisted 683 university students studying English as a foreign language. The data collection was conducted with the use the Metacognitive Awareness Inventory; and the students’ grades were also used. As a result, it was observed that there were no correlations between the metacognitive awareness and its sub-dimensions and the achiemevent in foreign language. Moreover, the only variable that predicted the academic achievement was monitoring skill.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Metacognitive awareness; Metacognition; Foreign language; Achievement